Sosialisasi tentang Pentingnya Pencegahan Kenakalan Remaja Kelas VI di SD Dharma Wanita 2024 - Sr. Sipayung R; Sinuraya E; Simatupang P; Situmorang R; Naibaho M; Sianipar O; Manik R; Damanik W (Universitas 45 Surabaya, 2024)
Journal of Community Education Service (JPPM) Volume 1, NO 1, March 2024 is a study that evaluates the impact of gadget use on the mental health of second grade students. This study aims to understand how excessive gadget use can affect the mental health of children in elementary school age. In this study, 200 students from five elementary schools participated in surveys and interviews to collect data on gadget use patterns and its impact on their mental health. The results showed that excessive gadget use can cause emotional and behavioral problems in children, such as anxiety, depression and sleep disturbances. The study also highlights the importance of parents' and educators' monitoring of the time and type of content accessed by children through gadgets, as well as their active role in educating children about healthy gadget use. The research methods used included structured surveys and in-depth interviews, which allowed researchers to gain a comprehensive understanding of students' experiences and perceptions regarding gadget use. In addition, this study also discusses the factors that influence excessive gadget use and juvenile delinquency prevention, emphasizing the important role of education and supervision in preventing the negative impact of gadget use.